2014
DOI: 10.1007/s00787-014-0665-1
|View full text |Cite
|
Sign up to set email alerts
|

Contextual variability of ADHD symptoms: embracement not erasement of a key moderating factor

Abstract: this is clearly below the clinical cut-off. Is a child with such a clinical profile not meaningfully different from a child exhibiting six or more symptoms in all settings? It has long been recognized that this is the case [22]. We argue that this vaguely defined criterion reflects a broader neglected issue of variability in number and contextual (in)stability of symptoms that is so typical in ADHD affected populations. We believe that variation in number and contextual expression of symptoms is a key factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(30 reference statements)
0
22
0
1
Order By: Relevance
“…This should be addressed in future research using multiple raters such as peers, parent, and self-reports, in addition to teacher reports. In particular, as there may be important contextual influences on the expression of ADHD symptoms (e.g., Rommelse et al, 2015), it will be important to obtain ratings from individuals who observe the target in different environments (e.g., home vs. school). Finally, ratings in the present study may have been affected by a “halo effect”: an inflation of intercorrelations because of a tendency to falsely ascribe symptoms to an individual who displays conceptually related symptoms (e.g., Hartung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This should be addressed in future research using multiple raters such as peers, parent, and self-reports, in addition to teacher reports. In particular, as there may be important contextual influences on the expression of ADHD symptoms (e.g., Rommelse et al, 2015), it will be important to obtain ratings from individuals who observe the target in different environments (e.g., home vs. school). Finally, ratings in the present study may have been affected by a “halo effect”: an inflation of intercorrelations because of a tendency to falsely ascribe symptoms to an individual who displays conceptually related symptoms (e.g., Hartung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This will enable to assess contextual variability of ADHD symptoms (Rommelse et al . 2015). Next, feedback can be provided to the patient, based on the sampled and processed data.…”
Section: Optimising Treatment Strategies In Adolescencementioning
confidence: 99%
“…Contextual differences in children’s clinical symptoms are increasingly recognized as reliable differences rather than measurement error (De Los Reyes et al, 2015; Rommelse et al, 2015). Some have suggested that ODD may be best conceptualized as informant-specific, because ODD identified by mothers only versus teachers only have different correlates (Drabick et al, 2007; Offord et al, 1996).…”
Section: Introductionmentioning
confidence: 99%